Design of Inclusive Green Open Spaces as a Medium for Intergenerational Social Interaction in Urban Areas (Journal of Social And Education Research, 2023)
. Inclusive green open spaces play a vital role in enhancing the quality of urban life by promoting social interaction, environmental sustainability, and psychological well-being. This study aims to explore the concept and design principles of inclusive green open spaces as a means of fostering intergenerational social interaction in urban areas. Using a literature review design, this research analyzes eight selected scientific articles published between 2010-2023 that discuss inclusive urban design, social interaction, and sustainable public spaces. The results indicate that inclusive design emphasizing accessibility, safety, comfort, and multifunctionality creates opportunities for interaction among various age groups and social backgrounds. Furthermore, the integration of ecological functions with social needs contributes to environmental sustainability and urban resilience. Community participation and universal design principles are identified as key elements in ensuring that green open spaces are equitable and responsive to the needs of all users. This study concludes that the development of inclusive green open spaces not only supports sustainable urban planning but also strengthens social cohesion and intergenerational connections within cities.